synthesis of Characterization and Biological Evaluation of Imidazole Derivatives and Benzoin Moiety - Mani Taneja, Dr. Anurekha Jain (International Journal of Advanced Science and Technology, 2020)
synthesis of Characterization and Biological Evaluation of Imidazole Derivatives and Benzoin Moiety